A 'sensitising' perspective on understanding students' learning experiences in case studies. Issue 2 (July 2022) - You, Jacqueline Jing
Abstract: The use of case studies in teaching is a common pedagogical approach in business and management education. Despite its prominent role in business schools, there is a longstanding debate between advocates and detractors over its usefulness in educating management and business students. In fact, evidence remains unclear as to whether students find case studies useful in their learning experiences. Drawing on the concept of sensitising in student engagement (SE) research, this paper aims to understand student's learning experiences in the case-based teaching environment in terms of four factors: learning agency, learning success, learning well-being and learning social justice. Based on classroom observations and in-depth interviews with international postgraduate students studying in the UK, the findings provide new insights into the usefulness of case studies in management teaching and lead to a number of research avenues to further examine the interrelationships identified. Highlights: Understanding student's learning experience in the case-based teaching environment. Student engagement research: learning agency, learning success, learning well-being and learning social justice. Bringing student's voice in the higher education. Leveraging case studies to develop student's network thinking, emotional intelligence and inter-cultural intelligence.